The Use of New Control Card for Health Education about Chemotherapy Procedures for Patients - Tumini Tumini (Health Notions, 2017)
In every stage of long and complex chemotherapy procedure, of course, it could confuse patients. The purpose of this queasy experimental research was to analyze the effect of education from nurses about chemotherapy procedure on patient's knowledge level toward the use of new card at one-stop oncology poly (POSA (Poli Onkologi Satu Atap)) of Dr. Soetomo Hospital, Surabaya, by using "pre-test post-test with control group design". The subjects were divided into two groups: treatment group that was given the education in using new cards and control group that was given the education in using old cards. The treatment group underwent the increase knowledge of general chemotherapy procedures, meanwhile, the control group did not undergo any increase. Keywords: Chemotherapy procedures, Knowledge, Patients, Education